The Existence of People's Consultative Assembly in Indonesian State System in the Pancasila Democracy Perspective - MARZUKI, Marzuki; SITOMPUL, Roswita (Journal of Advanced Research in Law and Economics; Vol 11 No 3 (2020): JARLE Volume XI Issue 3(49) Summer 2020DO - 10.14505/jarle.v11.3(49).30, 2020)
The sovereignty of the people is one of the principles of Indonesian state administration, contained in the Preamble and Articles in the 1945 Constitution of the Republic of Indonesia, implemented through the People's Consultative Assembly (MPR). But after the Amendment to the 1945 Constitution, the position of the MPR in the Proclamation Constitution has been placed as the highest state institution and the holder of popular sovereignty, and today based on the institutional structure of the state, the People’s Consultative Assembly (MPR) has been degraded becoming an equal institution with other State institutions. Such implications, which are certainly seen from a constitutional perspective, have injured Pancasila democracy, which is based on deliberation and consensus, resulting in no more oversight mechanisms that can be carried out against various state institutions, including the President, and this in turn has led to liberal democracy based on individualism. Therefore, a comprehensive study is needed to reinstate the MPR as the highest state institution and holder of popular sovereignty in the format of State institutions in Indonesia as a representation of all Indonesian people based on deliberation and consensus in every decision making.